The Dollar Auction Game: A laboratory comparison between Individuals and Groups - Andrea Morone; Simone Nuzzo; Rocco Caferra (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
The aim of this paper is to analyze bidders' behavior, comparing individuals and groups' decisions within the dollar auction framework. This game induces subjects to fall prey into the paradigm of escalation, which is driven by agents' commitment to higher and higher bids. Whenever each participant commits himself to a bid, the lower bidder, motivated by the wish to win as well as to defend his prior investment, finds it in his best interest to place a higher bid to overcome his opponent. The latter mechanism may lead subjects to overbid. We find that the Nash equilibrium of the game is only rarely attained. Second, we detect clean evidence that groups' decisions are, on average, superior to individuals' decisions. Learning over time is clearly evident, leading individuals to perform nearly as good as groups in the final rounds of the game.
Keywords: C91; 330; escalation; winner's curse